Divided Alliances: A Discussion of Inuit Resilience in Post-Secondary Education - Snow, Kathy; Obed, Diane; Lane, Jodie (Études Inuit Studies, 2023)
Although the Inuit high school completion rate has been climbing, the same cannot be said for Inuit participation in post-secondary education in Canada. This paper seeks to move beyond the obvious physical, and financial barriers to explore the colonial biases present in post-secondary institutions as further and more enduring challenges to access for Inuit. Through conversations with 10 Inuit post-secondary participants, graduates, and leavers, seven critical factors emerged. Viewed from the perspective of Inuit Qaujimajatuqangit, these factors identified where institutions have continued to fail students. The hope here is to raise greater awareness of the unparalleled challenges Inuit must face when choosing to participate in post-secondary education not only in terms of leaving home, but also of negotiating culture and the worldviews of Southern colonial learning institutions. Bien que le taux d’achèvement des études secondaires des Inuit soit en hausse, on ne peut pas en dire autant de la participation des Inuit à l’enseignement post-secondaire au Canada. Cet article cherche à dépasser les obstacles physiques et financiers évidents pour explorer les préjugés coloniaux présents dans les établissements d’enseignement postsecondaire, qui constituent des défis supplémentaires et plus durables pour l’accès des Inuit. Des conversations avec dix participants, diplômés et finissants inuit de l’enseignement postsecondaire ont permis de dégager sept facteurs critiques. Du point de vue de l’Inuit Qaujimajatuqangit, ces facteurs ont permis d’identifier les domaines dans lesquels les établissements ont continué à décevoir les étudiants. L’objectif est de mieux faire connaître les défis incomparables auxquels les Inuit doivent faire face lorsqu’ils choisissent de participer à l’enseignement postsecondaire, non seulement en quittant leur foyer, mais aussi en négociant la culture et les visions du monde des établissements d’enseignement coloniaux du Sud.